Origin and Trace of Hydrothermal Calcites in the Hydrocarbon Reservoirs Intruded by Diabase: Evidence From Strontium and Oxygen Isotopic Proxies - Liu, Chao; Xue, Rui; Jia, Zhiwei; Zhao, Xiaodong; Wang, Ke; Yang, Yong; He, Junhao; Liu, Ping; Liu, Zhigang (Frontiers in Earth Science, 2022)
Thermal contact clastic rocks provide a new potential type of hydrocarbon reservoirs for expanding exploration targets. However, the development mechanism of this type of reservoir remains enigmatic. Authigenic hydrothermal carbonates associated with magmatism exert significant controls over physical properties of the contact reservoirs. Therefore, the origin and trace of hydrothermal carbonates are key issues for reservoir development elucidation of thermal contact reservoirs and need to be further investigated. The current study takes the typical hydrocarbon area of thermal contact metasandstone reservoirs from the Funing Formation, northern Slope of Gaoyou sag, as a case study, aiming to unravel the origin and trace of authigenic hydrothermal calcites developed in thermal contact reservoirs, mainly using strontium and oxygen isotopic geochemistry proxies combined with petrological and mineralogical analyses. Authigenic hydrothermal calcites are distinguished, and their distribution characteristics are examined in thermal contact rocks. Subsequently, the origin and migration trace of the hydrothermal-related calcites are clarified. This study has significant implications for intensive understanding of reservoir development mechanism and reservoir evaluation and prediction of thermal contact clastic rocks.